2022
DOI: 10.3390/genes13030434
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of the Root Vole Microtus oeconomus: Resistance of the Habitat Specialist to the Natural Fragmentation of Preferred Moist Habitats

Abstract: Climate-related changes have a severe impact on wetland ecosystems and pose a serious challenge for wetland-dependent animals as their preferred habitats decline, lose spatial continuity, and appear as isolated islands in the landscape. In this paper, we studied the effects of long-term habitat changes (drying out and fragmentation of wet non-forest habitats) on the genetic structure of the population of the root vole Microtus oeconomus, a species preferring moist habitats. We intended to check what barriers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 71 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Genetic isolation also operates at a local scale [15], accentuating the impacts of climatechange-related alterations to wetland ecosystems and the desiccation of wet grasslands. Lopucki et al demonstrated that gene exchange between local populations of A. oeconomus is possible even when separated by several kilometers of unfavorable habitat, but anthropogenic barriers may exert a stronger isolating effect [10]. Population fragmentation is also prevalent in other countries, such as Hungary [18] and Austria [62].…”
Section: The Isolation Spread and Genetic Diversity Of Alexandromys O...mentioning
confidence: 99%
See 4 more Smart Citations
“…Genetic isolation also operates at a local scale [15], accentuating the impacts of climatechange-related alterations to wetland ecosystems and the desiccation of wet grasslands. Lopucki et al demonstrated that gene exchange between local populations of A. oeconomus is possible even when separated by several kilometers of unfavorable habitat, but anthropogenic barriers may exert a stronger isolating effect [10]. Population fragmentation is also prevalent in other countries, such as Hungary [18] and Austria [62].…”
Section: The Isolation Spread and Genetic Diversity Of Alexandromys O...mentioning
confidence: 99%
“…In our study, the two northern sites are situated in an anthropogenized landscape characterized by intensive agriculture and fragmented wet habitats. The dispersal potential of A. oeconomus may not be sufficient to counteract the genetic effects of isolation [10,57].…”
Section: The Isolation Spread and Genetic Diversity Of Alexandromys O...mentioning
confidence: 99%
See 3 more Smart Citations